2022
DOI: 10.3390/antiox11081618
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Hesperetin, Hesperidin and Hesperidin Glucoside: Antioxidant, Anti-Inflammatory, and Antibacterial Activities In Vitro

Abstract: The antioxidant, anti-inflammatory and antibacterial activities of hesperetin, hesperidin and hesperidin glucoside with different solubility were compared in vitro. Hesperetin was prepared by enzymatic hydrolysis from hesperidin, and hesperidin glucoside composed of hesperidin mono-glucoside was prepared from hesperidin through enzymatic transglycosylation. Solubility of the compounds was different: the partition coefficient (log P) was 2.85 ± 0.02 for hesperetin, 2.01 ± 0.02 for hesperidin, and −3.04 ± 0.03 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 75 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…Structurally, it is a flavonoid glycoside comprising hesperetin (HESP) and disaccharides. 22 Increasing number of studies have reported that HES exhibits a broad range of biological activities, like antibacterial, antioxidant, anti-inflammatory, 23 and antithrombotic functions. 24 In particular, HES has been confirmed using the RNase A-MGO assay model system as well to inhibit the generation of advanced glycation end products by capturing methylglyoxal (MGO, an RCS).…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it is a flavonoid glycoside comprising hesperetin (HESP) and disaccharides. 22 Increasing number of studies have reported that HES exhibits a broad range of biological activities, like antibacterial, antioxidant, anti-inflammatory, 23 and antithrombotic functions. 24 In particular, HES has been confirmed using the RNase A-MGO assay model system as well to inhibit the generation of advanced glycation end products by capturing methylglyoxal (MGO, an RCS).…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Table 1 , hesperetin, chlorogenic acid, and caffeic acid were reported as three compounds from PE with high concentrations. Hesperetin was obtained from the enzymatic hydrolysis of hesperidin and evaluated for antimicrobial activity against Gram-positive and Gram-negative bacteria, the results revealed that hesperetin more effectively inhibited the model microbes than hesperidin and hesperidin glucoside 46 . Yen et al 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous study of hesperetin has indicated its low inhibitory potential towards S. aureus (MIC > 1 mg/mL) [ 17 ], as confirmed also in this study (MIC > 4 mg/mL). Moreover, stronger antibacterial potential for hesperetin was noticed in the study of Choi et al [ 18 ], who determined MIC at 0.125 mg/mL, and in the study of Ivanov et al [ 19 ], with MIC 0.5 mg/mL, both towards S. aureus . In this previous study [ 19 ] hesperetin exhibited identical antibacterial potential as its glycoside hesperidin, suggesting that sugar moiety does not have impact on antibacterial properties of this flavonoid.…”
Section: Discussionmentioning
confidence: 98%